Intervention Effect of Oropharyngeal Administration of Colostrum in Preterm Infants: A Meta-Analysis - Huo, Mengyue; Liu, Chunli; Mei, Hua; Zhang, Yuheng; Liu, Chunzhi; Song, Dan; Zhang, Yayu; Zhang, Yanbo; Xin, Chun (Frontiers in Pediatrics, 2022)
Objective To evaluate the efficacy and safety of oropharyngeal administration of colostrum (OAC) in preterm infants. Methods We searched Embase, MEDLINE, Cochrane Central Register of Controlled Trials (CENTRAL), Cumulative Index to Nursing and Allied Health Literature (CINAHL), and the website of the clinical trials, search time was from the establishment of the databases or websites up to 1 February 2022. Preterm infants with gestational age (GA) ≤ 32 weeks or birth weight (BW) ≤ 1500 g were taken as the participants, collect randomized controlled trials (RCTs) of comparing OAC and placebo or no intervention in preterm infants. Two researchers independently screened the literature, extracted the data, and evaluated the quality of the literature, and we adopted Review Manager 5.3 software for meta-analysis. Results In total, 11 RCTs (n = 1,173) were included in the review. A meta-analysis showed significant difference in the incidence of necrotizing enterocolitis [NEC; p = 0.009, relative ratio (RR) = 0.51, 95% confidence interval (CI) = 0.31–0.84], late-onset sepsis (LOS; p = 0.02, RR = 0.75, 95% CI = 0.59–0.95), ventilator-associated pneumonia (VAP; p = 0.03, RR = 0.48, 95% CI = 0.24–0.95), the time to reach full enteral feeds (p < 0.00001, mean difference (MD) = −3.40, 95% CI = −3.87 to −2.92), duration of hospital stay (p < 0.00001, MD = −10.00, 95% CI = −11.36 to −8.64), and the rate of weight gain (kg.d; p < 0.00001, MD = 2.63, 95% CI = 2.10–3.16) between the colostrum group and control group. Meanwhile, researchers found no significant difference between the colostrum group and control group in the incidence of bronchopulmonary dysplasia (BPD; p = 0.17, RR = 0.83, 95% CI = 0.64–1.08), intraventricular hemorrhage (IVH; grade ≥3; p = 0.05, RR = 0.44, 95% CI = 0.19–1.01), periventricular leukomalacia (PVL; p = 0.67, RR = 0.70, 95% CI = 0.14–3.49), retinopathy of prematurity (ROP; p = 0.29, RR = 1.25, 95% CI = 0.82–1.89), and patent ductus arteriosus (PDA; p = 0.17, RR = 1.22, 95% CI = 0.92–1.62). Conclusion Oropharyngeal administration of colostrum can reduce the incidence of NEC, LOS, and VAP in preterm infants, shortening the time to reach full enteral feeds, and duration of hospital stay, and increasing the rate of weight gain (kg.d). Therefore, OAC can be used as part of routine care for preterm infants.